Effect of metabolic uncoupler, 3, 3′, 4′, 5-tetrachlorosalicylanilide (TCS) on Bacillus subtilis: biofilm formation, flocculability and surface characteristics. Issue 29 (1st May 2018) - Feng, Xiao-Chi; Guo, Wan-Qian; Zheng, He-Shan; Wu, Qing-Lian; Luo, Hai-Chao; Ren, Nan-Qi
Abstract : This study aimed to investigate the inhibitory mechanism of metabolic uncoupler on biofilm formation through surface characteristics and thermodynamics analysis. Abstract : In order to understand the inhibitory mechanism of metabolic uncoupler in biofilm, this study investigated the effect of TCS on B. subtilis biofilm formation, flocculability, surface characteristics and thermodynamic properties. An optimal concentration of TCS, a metabolic uncoupler, was observed to substantially inhibit biofilm formation and the secretion of extracellular polymeric substances (EPS). The effect of TCS on the zeta potential and flocculability of bacterial suspension implied the addition of 100 μg L −1 TCS increased the net negative charge of cell surface which induced the reduction of B. subtilis flocculability. Meanwhile, the effects of TCS on bacterial surfacial thermodynamic properties were analyzed by the Derjaguin–Landau–Verwey–Overbeek (DLVO) and extend DLVO (XDLVO) theories. As DLVO and XDLVO predicted, the primary energy barrier between bacterial cells incubated with 100 μg L −1 TCS were increased compared to that of control, indicating that B. subtilis incubated with 100 μg L −1 TCS must consume more energy to aggregate or form biofilm.